The Effect of Delphi-based Learning Media on the Students’ Learning Outcomes in Electricity and Electronic Lessons Reviewed from the Level of Independence Learning Students - Bagus Dwi Cahyono; Supari Muslim; Joko Joko; Bima Anggana Widhiarta P (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2019)
The purpose of this study is to: (1) analyze the differences in learning outcomes between students who study using Delphi-based learning media and students who learn by using Power Pont learning media in Basic Electrical and Electronics subjects at Surabaya KAL-1 Vocational School; (2) analyze the differences in learning outcomes in Basic Electrical and Electronics subjects between students who have a high level of learning independence and students who have a low level of learning independence at Surabaya KAL-1 Vocational School; (3) analyzing the interaction between the use of instructional media (delph and PPT) and the level of learning independence on learning outcomes in the Basic Electrical and Electronics subjects at the Surabaya KAL-1 Vocational School. This type of research is quasi-experimental using factorial 2x2 design, and the data were analyzed using Anacova two lines with the help of SPSS. The study found: (1) Learning outcomes for students using Delphi-based learning media (cognitive domain mean = 79) were significantly higher than learning outcomes for students who used Point Power learning media (cognitive domain = 73) in Basic Electricity subjects and Electronics at KAL 1 SMK Surabaya; (2) Learning outcomes for students who have TKBT (cognitive domain average = 78.17) are significantly higher than learning outcomes for students who have TKBR (cognitive domain average = 74.35) in Basic Electrical and Electronics subjects at KAL Vocational School. 1 Surabaya; (3) there is a significant interaction between the use of learning media (Delphi and PPT) and the level of learning independence on cognitive learning outcomes in the Basic Electrical and Electronics subjects at the Surabaya KAL-1 Vocational School. Research suggests: (1) Selection of learning media should be done appropriately especially if the school already has adequate infrastructure; (2) teachers in learning must be able to pay attention to the characteristics of students (learning independence) so that students are able to master the material better; and (3) learning media as a source of learning must be able to be maximally utilized by students in its use.